To sell or not to sell: Country food markets and Inuit identity in Nunavut. Issue 3 (1st October 2016) - Searles, Edmund (Ned)
ABSTRACT: Problems and opportunities associated with the sale of country food (subsistence-based food obtained through hunting, fishing, and gathering) provide a touchstone for ongoing debates about Inuit and non-Inuit identity in the Canadian Arctic, as well as how to respond to high rates of food insecurity and poverty that continue to affect many families and households in the region. Hunting, fishing, gathering, and sharing food are all considered typical of what Inuit do (or should do) but what non-Inuit typically don't do. In this article, I examine what Inuit think of selling country food and why. Based on long term anthropological research on the cultural politics of food and foodways in Iqaluit, the capital of Nunavut, Canada, this article analyzes a range of perspectives concerning the sale of country food, revealing an array of symbols and stereotypes that undergird local beliefs about the cultural significance of country food and its link to the future of Inuit identity.